Stimulus generation for RF MEMS switches test application. (1st January 2012) - Song, Mingxin; Yin, Jinghua; Cao, Zuobao; Wu, Tong; Zhao, Yu; Jin, Zhao; Zjajo, Amir
The sinewave generators based on switched-capacitor (SC) technologies are implemented in transistor level. This analogue sinewave generator consists of two parts: an approximate sinewave generator and a filter. The structure of this generator is robust and easily-controlled, in which an approximate sinewave is firstly generated based on SC circuits and then filter the harmonics. The main advantages of the approach are that both the amplitude and the frequency of the signal can be controlled by a DC input voltage and the clock frequency respectively. The amplitude of the sinewave is 400 mV with SNR of 42.2 dB at a supply voltage of 1.2 V. The settling time of the system is less than 0.5 u and the power is less than 5 mW.